THE KNOWLEDGE AND ATTITUDE AMONG MEDICAL STUDENTS TOWARD RADIATION ONCOLOGY AS A SPECIALTY IN A GOVERNMENT MEDICAL COLLEGE IN SOUTH COASTAL ANDHRA PRADESH - AN OBSERVATIONAL STUDY - BUDURU PADMAVATHI; SIRISHA NP; KONDETI MADHAVI; THALUPULA INDRAJA NAIDU; GUDE HARI PRIYA; MOTTIKAYALA VARSHITH; MOTTIKAYALA SAI AKHIL (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Medical education is a continuously evolving field. Despite the radiation damage to normal cells, radiotherapy (RT) has emerged as an inevitable option for moderate-to-advanced stages of cancer. This highlights the need for radiation oncology for the growing oncology patient community. The present observational study assessed the 468 male and female Bachelor of Medicine and Bachelor of Surgery (MBBS) students’ knowledge and attitude towards radiation oncology as a specialty at A.C. Subba Reddy Government Medical College, Nellore, Andhra Pradesh, during the period of May–June 2024. The outcome measure of this study was the participants responses to a simple, internally validated, 18-item questionnaire. Four hundred and sixty-seven students completed the questionnaire and communicated via the same medium they received. The mean age of the male and female participants was 20.47 ± 1.42 and 20.37 ± 1.39, respectively. Data analysis revealed that, among participants, 312 (133 males and 179 females) knew RT was part of their curriculum. However, 70 students reported never knowing it, and 143 were never assessed on their knowledge. Despite RT being the second most preferred postgraduate field, students cited a lack of awareness about career prospects and inadequate undergraduate exposure as major barriers. Students recommended early curriculum integration, increased exposure, and more RT departments in government hospitals to attract bright students to the field. The findings of the present study reveal that efforts from regulatory bodies like the National Medical commission (NMC) are essential to enhancing awareness, training, and facility standards to guide more students toward radiation oncology.